Non-pancreatic retroperitoneal pseudocyst: a rare case report - Karuppusamy, Shankar; Vaithianathan, Rajan (International Surgery Journal, 2024)
A retroperitoneal pseudocyst is usually pancreatic in origin. Non-pancreatic retroperitoneal pseudocyst has a very low incidence, primarily benign and usually asymptomatic. The absence of epithelial lining in the cyst wall characterizes the pseudocyst. The absence of epithelial lining in the cyst wall characterizes the pseudocyst. Here, we report a case of a 53-year-old male patient who presented to OPD with mass per abdomen and lower abdomen pain. The computed tomography scan of the abdomen and pelvis revealed a retroperitoneal cyst abutting the right psoas muscle. The patient underwent an open excision of a retroperitoneal cyst. Histopathological examination of the specimen showed a non-pancreatic retroperitoneal pseudocyst. It is a rare case; very few cases have been reported in the literature. One such case is reported here.